Reformation and Reallocation: Religious and Secular Economic Activity in Early Modern Germany - Davide Cantoni; Jeremiah Dittmar; Noam Yuchtman (Center for Economic Studies and ifo Institute (CESifo), 2016)
The Protestant Reformation, beginning in 1517, was a first-order economic shock. We document its effects on the sectoral allocation of economic activity in Germany using highly disaggregated data. During the Reformation, particularly in Protestant regions, large numbers of monasteries were expropriated. University graduates shifted toward secular, rather than religious, occupations. Forward-looking university students shifted away from the study of religious sector-specific theology, toward secular fields. Construction activity in the religious sector declined, particularly in Protestant regions, while secular construction increased. These findings highlight the unintended consequences of the Reformation—a religious movement that contributed to Europe's secularization.
Keywords: N13; N33; J24; E02; 330; protestant reformation; sectoral allocation; human capital